Multiphase flow dynamics and mass transfer in different multiphase reactor for shear controllable synthesis process - Guo, Yanqing (2021)
In short, this thesis gives insight in detailed particle synthesis process modelling in two main multiphase reactors (IJR and SVFR) and experiments of synthesis of FePO4 and SiO2 aggregated particles are performed to analysis effect of hydrodynamics on particle properties. The attempt of combination of fast-mixer and external ultrasound field in micro/nano-particle synthesis has successfully intensified turbulence and such combination has positive effects on aspects of chemical reaction, mixing performance and mass transfer. Except for experimental work, the simulation work has been carried out to analyse flow patterns, turbulent intensity, chemical reaction as well as particle fluid interaction in particle synthesis process in multiphase reactors. Such investigation makes it possible to build correlations on hydrodynamic parameters and particle characteristics and helps to predict the behaviour and properties of particles. This is meaningful for design, upgrade and scale-up of multiphase reactor in synthesis process.